If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x+1x)+7-5x=8(-5)(5x-6x)+23
We move all terms to the left:
4(3x+1x)+7-5x-(8(-5)(5x-6x)+23)=0
We add all the numbers together, and all the variables
4(+4x)-5x-(8(-5)(-1x)+23)+7=0
We add all the numbers together, and all the variables
-5x+4(+4x)-(8(-5)(-1x)+23)+7=0
We multiply parentheses
-5x+16x-(8(-5)(-1x)+23)+7=0
We multiply parentheses ..
-5x+16x-(8(+5x)+23)+7=0
We calculate terms in parentheses: -(8(+5x)+23), so:We add all the numbers together, and all the variables
8(+5x)+23
We multiply parentheses
40x+23
Back to the equation:
-(40x+23)
11x-(40x+23)+7=0
We get rid of parentheses
11x-40x-23+7=0
We add all the numbers together, and all the variables
-29x-16=0
We move all terms containing x to the left, all other terms to the right
-29x=16
x=16/-29
x=-16/29
| 9f=918 | | w/28=17 | | 5h=100 | | 5^(2x+3)=4 | | 78=2z | | y^2+28y+60=0 | | 8+5^(2x+3)=12 | | 130+10x=18x | | x+(x+5)+1/3x=0 | | y/5.5=90 | | 1.3c+5.2=6.4 | | G(-2)=3x-1 | | 2p-5p=3 | | 4+2x-3x=-2 | | 130+20x=36x | | 65+10x=18x | | 130+20x=18x | | 4x^2+11x-6=x^2-2 | | 114=5-(2-x) | | Z=6-3x | | 130=18x | | 3-3a-4=-5 | | 5(2.5^x)=10 | | x2−6x−12=0 | | f=33/2(50) | | f=33/2(50)+9.24 | | Z=p | | 0.12x+56-(2830/x^2)=0 | | 15x=56+8x | | 1/8x+8=11 | | (n)(n-1)(n-2)(n-3)(n-4)=0 | | 4q-2q=18 |